Electrophoretic deposition of chitosan/gelatin coatings with controlled porous surface topography to enhance initial osteoblast adhesive responses. Issue 47 (14th November 2016) - Zhang, Zhen; Cheng, Xian; Yao, Yao; Luo, Jiaxin; Tang, Qingming; Wu, Hongling; Lin, Sihan; Han, Changjun; Wei, Qingsong; Chen, Lili
Abstract : This study developed a method to fabricated electrophoretic deposited coatings with controllable porous surface topography via controlling bubble generation to enhance initial osteoblast adhesive responses. Abstract : Electrophoretically deposited (EPD) coatings have often been employed recently for the addition of different new chemical compositions to classic chitosan coatings to improve the biocompatibility and therapeutic potential of coated implants. However, little attention has been paid to enhance the cell response to EPD coatings via integrating the effects of chemical components and surface topography. Here, we fabricated EPD chitosan/gelatin (CS/G) coatings with controlled porous surface topography by controlling bubble generation in the EPD process via changing the gelatin content in solution from 0, 0.01, 0.1, and 1 to 10 mg ml −1 . The pure chitosan coating surface was characterized by homogeneous large pores of 500 μm. After 0.01 mg ml −1 gelatin was added, 180 μm small pores appeared on the walls of large pores. As the gelatin content increased to 0.1 mg ml −1, a number of small pores increased noticeably. When the gelatin content reached 1 mg ml −1, large pores disappeared, and the coating displayed homogeneous small pores. 10 mg ml −1 gelatin concentration led to coatings consisting of small pores with not integral and continuous structures. The initial osteoblastic responses, including cell adherence progress, spreading area, proliferation rate, and focal adhesion-related gene expression, gradually improved from 0 to 0.01, 0.1, and 1 mg ml −1 gelatin content, but decreased from 1 to 10 mg ml −1 . All these results indicated that the initial cell responses to coatings reached a peak when it was 1 mg ml −1 gelatin and they had homogeneous small pores, which might contribute to the synergistic effects of the porous surface structure and components. This work would be beneficial for expanding the potential application of EPD coatings.